The Role Of Mobile Phones In The Development Of Social Capital Among Refugees In South Africa. Issue 1 (5th December 2017) - Bacishoga, Kasky B.; Hooper, Val A.; Johnston, Kevin A.
Abstract: Mobile phones have been identified as possible tools to aid in refugee integration into new countries. Using a social capital theoretical lens, the role of mobile phones in the development of social capital among refugees in South Africa is explored. Semi‐structured interviews were conducted with 29 refugees in South Africa. Findings indicate that mobile phones can play an important role in the development of bridging social capital thereby aiding in the social and economic integration of refugees into the community. Mobile phones also play an important role in developing bonding and maintained social capital but these tend to be with their homeland nationals rather than the local community. Reasons for the development of the negative social capital are explored, whether they are attributable to the authorities or to the refugees themselves. Insights are provided into how mobile phones can be used to enhance the development of social capital among refugees.